CanIMPACT: Understanding complexities, variation, and disparities in the breast cancer care continuum in Five Canadian provinces using administrative data - Patti Groome; Marcy Winget; Li Jiang; Kathleen Decker; Cynthia Kendell; Monika Krzyzanowska; Dongdong Li; Aisha Lofters; Mary L McBride; Nicole Mittmann; Rahim Moineddin; Geoff Porter; et al. (International Journal of Population Data Science, 2017)
ABSTRACT